2015
DOI: 10.3390/en8021440
|View full text |Cite
|
Sign up to set email alerts
|

Monetization of External Costs Using Lifecycle Analysis—A Comparative Case Study of Coal-Fired and Biomass Power Plants in Northeast China

Abstract: Abstract:In this study, the structures of external costs are built in line with coal-fired and biomass power plant life cycle activities in Northeast China. The external cost of coal-fired and biomass power plants was compared, using the lifecycle approach. In addition, the external costs of a biomass power plant are calculated for each stage for comparison with those of a coal-fired power plant. The results highlight that the external costs of a coal-fired plant are 0.072 US $/kWh, which are much higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Given that China has begun to promote the large-scale deployment of electric vehicles (EVs), electricity demand is expected to increase rapidly and significantly in the future [9]. Therefore, some researchers have reported that if no active measures are taken, the carbon emissions from the power sector in China will increase to 6 billion tons in 2020 [10]. Coal-fired power generation is an important air pollution-induced factor that causes the notorious nationwide fog and hazy weather in autumn and winter [11].…”
Section: Dilemma In the Reduction Of Carbon Emissions From China's Pomentioning
confidence: 99%
“…Given that China has begun to promote the large-scale deployment of electric vehicles (EVs), electricity demand is expected to increase rapidly and significantly in the future [9]. Therefore, some researchers have reported that if no active measures are taken, the carbon emissions from the power sector in China will increase to 6 billion tons in 2020 [10]. Coal-fired power generation is an important air pollution-induced factor that causes the notorious nationwide fog and hazy weather in autumn and winter [11].…”
Section: Dilemma In the Reduction Of Carbon Emissions From China's Pomentioning
confidence: 99%
“…Wang et al [26] compared the external costs of power plants fired by coal versus biomass in a stylized life cycle approach. The (hard) coal mining part of their external cost quantification accounts for gangue, water contamination, methane emissions and occupational mortality and morbidity, and the quantification of these impacts follows a top-down approach.…”
Section: Previous Researchmentioning
confidence: 99%
“…After nearly 100 years of modern coal mining activities in mainland China, a large number of coal basins are facing a series of problems from multiple aspects. In the past thirty years, coal resources in the northeast China region have been on the verge of depletion, and many cities such as those in the Songliao Basin, Mohe Basin, and Hailaer Basin, are currently being forced to transform themselves from a traditional single coal-oriented economy structure [3]. Compared to these basins, basins located in the eastern region or southern region are also facing serious problems, with the most urgent one being the large annual increase in the mining depth (6-12 m/year) because of resource exhaustion near the ground surface.…”
Section: Introductionmentioning
confidence: 99%